The Impact of the Nationalization of the Suez Canal in 1956 on US-Panamanian Relations - Shattab, Ass.Prof Dr.Abdullah Muslim (Thi Qar Arts Journal, 2023)
The research studies the impact of the Nationalization of the Suez Canal in 1956 on the US-Panamanian relations, as the relations between the two countries witnessed tensions at the popular and diplomatic levels, and it came to the matter that the Panamanian government raised its voice loudly by demanding its canal, similar to what the Egyptians did in terms of nationalization, and the matter was further complicated by the call for the London Conference , which was held in the wake of Gamal Abdel Nasser's Nationalization of the Suez Canal, and not inviting Panama was a shock to the latter, although it has a global channel used by most countries for commercial  purposes   .